PENGARUH BELANJA PENDIDIKAN, BELANJA KESEHATAN DAN BELANJA INFRASTRUKTUR TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) (STUDI PADA 22 KABUPATEN/KOTA DI NTT) - Ratuludji, Stefanus Paulus; Preseveranda, Preseveranda; Man, Stanis (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to (1) determine the effect of education spending on the Human Development Index during the Covid-19 pandemic in East Nusa Tenggara Province; (2) determine the influence of health spending on the Human Development Index during the Covid-19 pandemic in East Nusa Tenggara Province; and (3) determine the effect of infrastructure spending on the Human Development Index during the Covid-19 pandemic in East Nusa Tenggara Province. The scope of this research is an analysis of the influence of government spending on education, health and infrastructure spending on the Human Development Index during the Covid-19 period in districts/cities in East Nusa Tenggara Province. The data analysis technique used in this research is panel data regression analysis using the Fixed Effect Model (FEM. The results of this research show that (1) partially education spending has a positive and significant effect on the human development index, partially health spending has a positive and significant effect on the index human development, partially infrastructure spending has a negative and significant effect on the human development index; (2) Simultaneously education spending, health spending and infrastructure spending have an effect on the human development index; and (3) the results of the determinant coefficient test (R2) show education spending, Health spending and infrastructure spending have an influence on increasing the human development index.